Analysis of symbol-centered interpretations in Attar's poetry - Majid Rastandeh; Vahid Mobarak (مطالعات زبانی و بلاغی)
The history of mystic Persian literature makes outstanding perspectives for us, especially when it's connected to Quran and Hadith. The mystic authors and poets have emphasized the common gaining from these two main sources of Islam and have recommended it throughout the years. They also encourage others to use these sources with their especial artistic look. Attar Neishabouri is one of these kinds of authors. In his poems facing the Quran and narrations, he has an interpretative and Belaghat-centered look in addition to the common look. This study is tended to introduce examples of symbol-centered and Belaghi interpretations with a descriptive-analytic method. Surveys show that in Attar's poetry some of the symbols such as Gheble, the verse of light, the story of Ibrahim and the fight with Namroud, the slaughter of Ismail, Feron, and Gharoun, have a significant effect that elucidates his especial care to the history of prophets. It has also been seen that sometimes Attar links mythological and mystical symbols in his interpretations to present his mystic thoughts. In other times the insane savants become his speakers for protesting the disorderly of the society.